Avulsion Fractures of the Calcaneal Tuberosity: A Single-Center Review of Outcomes and Complications. (December 2021) - Doany, Michael; Garcia, Alexander; Komatsu, David; Divaris, Nicholas; Kottmeier, Stephen; Paulus, Megan
Abstract : Objectives: The goal of this investigation was to determine the incidence of complications and revision surgery after calcaneal tuberosity avulsion fractures, to describe experience with different fixation constructs, and to compare revision surgery rates between tuberosity and tongue-type fractures of the calcaneus. Design: This was a retrospective study at a single level 1 trauma center between 2001 and 2019, including patients with calcaneal tuberosity avulsion fractures compared with patients with calcaneal tongue-type fractures. Results: Twenty-nine tuberosity fractures (23 surgical and six nonsurgical) and 37 tongue-type fractures (29 surgical and eight nonsurgical) were treated during the study period. Revision surgery was more common in the tuberosity group (26% versus 7%, P = 0.013). In the tuberosity group, 35% experienced some degree of implant failure, with 13% catastrophic loss of reduction and 22% loss of initial reduction with eventual union. Fragment size and initial displacement were not associated with revision surgery. No patients with implant failure noted in the tongue-type group. Discussion: Calcaneal tuberosity fractures showed significantly higher rate of revision surgery and failure of fixation compared with tongue-type fractures.